Phonon excitations in the quasi-one-dimensional Haldane phase of SrNi2V2O8 - Kurnosov, V.; Gnezdilov, V.; Lemmens, P.; Pashkevich, Yu.; Bera, A.K.; Islam, A.T.M.N.; Lake, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Vibrational Raman spectra of a single crystal of the coupled Haldane chain compound SrNi2V2O8 with uniaxial anisotropy were investigated in the 10–1000 cm−1 frequency range at temperatures 7–300 K. No structural phase transition was observed. The number of phonon lines observed in the experiment and their intensity were analyzed on the basis of the local symmetry considerations of different structural complexes. This approach was successful in explaining the discrepancy between the numbers of expected and experimentally observed phonon lines. Closeness of a real arrangement of some structural units to higher symmetry than the Wyckoff position results in strong interferential quenching of a number of Raman lines in the spectra.